Patients with multiple sclerosis do not necessarily consume more alcohol or tobacco than the general population - Yara Dadalti Fragoso; Sidney Gomes; Marcus Vinicius M. Goncalves; Suzana C. Nunes Machado; Rogerio de Rizo Morales; Francisco Tomas M. de Oliveira; João Filipe de Oliveira; Neide R. Simoes Olmo; Monica K. Fiuza Parolin; Fabio Siquineli; Patrick N. Stoney (Arquivos de Neuro-Psiquiatria)
Purpose Recent papers suggest that patients with multiple sclerosis (MS) are prone to alcohol misuse. This may be due to the combination of a lifelong and disabling disease with a psychiatric profile typical of MS. The objective of the present study was to assess these findings in a culturally different population of patients with MS.Method The present case-control transversal study assessed 168 patients with MS and 168 control subjects from Brazil.Results There were no evidence that patients with MS drank more alcohol or, smoked more than did controls. In fact, control subjects had a significantly higher alcohol consumption. The only trait associated to higher alcohol consumption was anxiety, both for patients and controls.Conclusion Unlike previous reports in the literature, patients with MS in our study did not drink or smoked more than a control population.